Effect of orchard floor management practices on growth, yield, leaf and soil nutrients in nectarine (Prunus persica) - SHARMA, SUMEET; SHARMA, D P (The Indian Journal of Agricultural Sciences, 2019)
The present investigation was carried out to assess the impact of different orchard floor management practices on growth, yield, leaf and soil nutrients in nectarine cv. Snow Queen. The maximum increase in annual shoot growth (65.05 cm), trunk girth (11.17%), tree height (13.25%), tree volume (41.10%), yield (59.59% was recorded under black polythene mulch. Maximum leaf area (31.40 cm2) and total chlorophyll (2.62 mg/g fresh weight) were observed under bicolour polythene mulch. Maximum leaf macro nutrient [N (2.73 %), P (0.22%), K (2.17%), Ca (1.90%), Mg (0.59%), soil nutrient [available N (355.92 kg/ha), P (40.74 kg/ha), K (367.78 kg/ha), exchangeable Ca (2.86 cmol (P+)/kg) and Mg (2.91 cmol (P+) /kg)] and soil organic carbon (2.09%) content were recorded under grass mulch. Black polythene mulch and bicolour polythene mulches are the best orchard floor management options for rainfed areas of Himachal Pradesh.